Taxonomy of coccids (Hemiptera: Coccidae: Coccus L.) associated with Crematogaster ants (Hymenoptera: Formicidae) in the stems of Macaranga plants (Euphorbiaceae) in Southeast Asia - Gullan, Penny J.; Kondo, Takumasa; Fiala, Brigitte; Quek, Swee-Peck (Zootaxa, 2018)
The Southeast Asian soft scale insects (Hemiptera: Coccomorpha: Coccidae) associated with ants of the Crematogaster borneensis-group (Hymenoptera: Formicidae) and living in the hollow stems of Macaranga plants (Euphorbiaceae) are revised taxonomically. Ten species of the genus Coccus L. are recognised: seven were described previously and three new species are described herein. The species are: Coccus caviramicolus Morrison, C. circularis Morrison, C. heckrothi Gullan & Kondo sp. n., C. lambirensis Gullan & Kondo sp. n., C. macarangicolus Takahashi, C. macarangae Morrison, C. penangensis Morrison, C. pseudotumuliferus Gullan & Kondo sp. n., C. secretus Morrison and C. tumuliferus Morrison. All of these species are described or redescribed and newly illustrated based on the adult females, and a key to distinguish the species is provided. We designate a lectotype for C. macarangicolus. The first-instar nymphs of all species are morphologically extremely similar and therefore only the first-instar nymph of C. macarangae is described and illustrated. Seven of these species currently are known only from Macaranga, but C. macarangae, C. secretus and perhaps C. pseudotumuliferus have been recorded from the hollow stems of several other ant-plants and a few non-myrmecophytes. The Coccus species from Macaranga are closely related to C. hesperidum L., the type species of the genus, and therefore are retained in the genus Coccus even though the adult females exhibit a few morphological differences from C. hesperidum. The species of Coccus from Macaranga appear to be parthenogenetic because no male nymphs or adults have been found, despite extensive collecting.